Use of Molasses-Based Blocks to Modify Grazing Patterns and Increase Highland Cattle Impacts on Alnus viridis-Encroached Pastures - Svensk, Mia; Nota, Ginevra; Mariotte, Pierre; Pittarello, Marco; Barberis, Davide; Lonati, Michele; Allan, Eric; Perotti, Elisa; Probo, Massimiliano (Frontiers in Ecology and Evolution, 2022)
Alnus viridis is a pioneer species that has expanded in Central Europe in the last decades, causing a series of negative agro-environmental impacts. Robust livestock grazing could be used as a targeted tool to reduce its encroachment, but more information is needed to find the best approach to achieve this goal. In this study, we assessed the potential of molasses-based blocks (MB) to lure Highland cattle into A. viridis-encroached areas and monitored impacts on the vegetation after grazing. In 2019 and 2020, two Highland cattle herds equipped with GPS collars were placed in three paddocks in the Swiss and Italian Alps, differing in the degree of A. viridis encroachment. In 2020, MB were added to highly encroached areas within each paddock to attract the herds to feed on A. viridis. Botanical surveys were carried out before and after grazing, around MB and control areas. Highland cattle grazed significantly more around MB (up to 50 m from the MB) compared to the previous year (i.e., same area without MB) and compared to control areas. The increased targeted grazing around MB led to a significant decrease in herbaceous cover and an increase in bare soil compared to control areas. Livestock grazing and trampling significantly reduced the cover of ferns, tall herbs, medium and small herbs, and woody species around MB compared to control areas. A. viridis leaves and branches were significantly removed and damaged up to 10 meters from the MB, due to the more intense livestock grazing. Such results highlight the potential of this management regime to effectively reduce A. viridis encroachment in montane grasslands.